2020
DOI: 10.1021/acs.chemrev.9b00449
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Difference Spectroscopy of Proteins: From Bands to Bonds

Abstract: Infrared difference spectroscopy probes vibrational changes of proteins upon their perturbation. Compared with other spectroscopic methods, it stands out by its sensitivity to the protonation state, H-bonding, and the conformation of different groups in proteins, including the peptide backbone, amino acid side chains, internal water molecules, or cofactors. In particular, the detection of protonation and H-bonding changes in a timeresolved manner, not easily obtained by other techniques, is one of the most suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
173
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(179 citation statements)
references
References 840 publications
(3,057 reference statements)
6
173
0
Order By: Relevance
“…1b), with expected bands at ~1700-1680 cm −1 and at ~1530-1500 cm −1 in aprotic organic solvents of low/medium polarity. 44 Upon considering the expected wavenumber and absorption coefficient of these vibrations relative to those of the amide backbone group, 42 we concluded that both peptides are roughly 85% α-helical.…”
Section: Resultsmentioning
confidence: 95%
“…1b), with expected bands at ~1700-1680 cm −1 and at ~1530-1500 cm −1 in aprotic organic solvents of low/medium polarity. 44 Upon considering the expected wavenumber and absorption coefficient of these vibrations relative to those of the amide backbone group, 42 we concluded that both peptides are roughly 85% α-helical.…”
Section: Resultsmentioning
confidence: 95%
“…However, analysing bands of low absorbance or overlapping signals, efficient trigger concept must be devised to compute accurate FTIR difference spectra. 49 Besides illumination, solvent exchange, and potential jump experiments [59][60][61] , I introduced quantitative gas titrations as a novel trigger strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Deuteration and hydration are mutually reversible, as demonstrated in Figure 7D. Understanding H/D isotope effects is key to understanding hydrogen bonding interations 49 and hydride chemistry. 65 The relation between sample concentration and sample film quality is not straight-forward and should be evaluated for each sample individually.…”
Section: Preparation Of Protein Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…protein fold) in a label-free manner. 1,2 Applications range from assignment of bacterial species, 3 detection of light-induced changes in protein conformation, cofactors and protonation state of individual amino acid residues, 4,5 aggregation states of proteins related to neurodegenerative diseases like Alzheimer's or Parkinson's disease [6][7][8] , and label-free imaging of tissue in cancer diagnosis. [9][10][11] On top of structural information, the temporal resolution of IR spectroscopy matches the decay times of vibrational modes in the femtosecond range.…”
mentioning
confidence: 99%